Effect of betaine supplementation on haematology, serum enzymes and hormone profile in gestating sows - MISHRA, ALOK; VERMA, A K; DAS, ASIT; SINGH, PUTAN; SAHOO, N R (The Indian Journal of Animal Sciences, 2019)
The study was conducted to study the effect of betaine supplementation on haematology, serum enzymes and hormones profile in gestating sows. For the study, artificially inseminated 18 crossbred (Landrace × Desi) sows were randomly distributed into 3 groups with 6 sows in each following a completely randomized design (CRD). Group T0 was fed with basal diet (control) and betaine was supplemented in group T1 and T2 @ 3 g/kg basal diet during late pregnancy (d 76 onwards till parturition) and throughout the length of gestation, respectively. The results revealed that betaine supplementation had no significant effect on the haemoglobin (Hb), packed cell volume (PCV), red blood cell (RBC) count, platelet count and white blood cells (WBC) count. Similarly, the serum enzymes such as aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phoshatase (ALP), lactate dehydogenase (LDH), and creatine kinase (CK) revealed no significant effect of betaine supplementation. The serum concentration of T3 and T4 hormone (ng/ml) of sows was significantly higher at the time of farrowing compared to the level at the time of insemination. The serum concentration of cortisol (ng/ml) of sows was significantly reduced in betaine supplemented groups compared to control. Thus, based on the results pertaining to cortisol levels in gestating, sows it can be concluded that betaine supplementation @ 3 g/kg diet, 76 day post insemination is beneficial to ameliorate the oxidative stress during pregnancy.